AB0502 All-Cause Hospitalizations in Systemic Lupus Erythematosus from A Northern Italian Referral Centre. (10th June 2014) - Bortoluzzi, A.; Padovan, M.; De Stefani, E.; Govoni, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic disease with a variable course. Although the mortality rate has been reduced in the last decades, the clinical management of lupus patients is extremely complex and affected by morbidities, directly or indirectly, related to the disease. Objectives: To estimate the rate of hospitalization in a cohort of patients with SLE from a Hub and Spoke referral centre in a Northern Italian district. To determine morbidity and mortality in this retrospective cohort of hospitalized SLE patients. Methods: A retrospective analysis of all hospitalizations was done using the discharge ICD-9-MC coding system to identify all patients admitted with a diagnosis of SLE between January 1999 and December 2011 (12 years). Results: After the retrospective chart review we included 366 patients for a total of 1051 admissions recorded in a time interval of 11 years. The mean age of patients at the time of hospitalization was 52.5 years (17.2 ±SD), 88.5% of patients were female. The most common reason of hospitalization, recorded in 51.9% of cases, was due to a disease related flare (at the onset or during the course of the same). The major comorbidities and complications reported were the following: cardiovascular (15.9%), haematological (9.7%), infectious (9.2%), renal (6.8%), neurological (5.9%). Hospitalizations associated with the coexistence of malignancies were reported in 7.6% of the cases, benign in 27/80 (33.7%). The mean hospitalization length was 11.4 days (11 ±SD). The annual rate of mortality was estimated as between 3% and 9% per year. Conclusions: In this retrospective study SLE flares remain the main reason for hospitalization. This is aligned to what literature reports (range 11.8 - 80.8%). The proportion of cardiovascular diseases represents the most prevalent complication recorded with heavy increase in the cost of illness and public spending. Considering the relative young age of our population, this finding emphasizes the need for greater attention to this complication in the management of lupus patient in early stages of disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4904